2017
DOI: 10.1093/mnras/stx1744
|View full text |Cite
|
Sign up to set email alerts
|

On the use of variability time-scales as an early classifier of radio transients and variables

Abstract: We have shown previously that a broad correlation between the peak radio luminosity and the variability time-scales, approximately L ∝ τ 5 , exists for variable synchrotron emitting sources and that different classes of astrophysical source occupy different regions of luminosity and time-scale space. Based on those results, we investigate whether the most basic information available for a newly discovered radio variable or transient -their rise and/or decline rate -can be used to set initial constraints on the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
0
4
1
Order By: Relevance
“…V404 Cyg, V6461 Sgr and H1743-322; Han & Hjellming 1992;Hjellming et al 2000;McClintock et al 2009) or periods of stable radio flux (GRS 1915+105;, which are more consistent with the timescale of VTC J095517.5+690813. However, typical LMXB minimum energies are also at least an order of magnitude lower than our estimate for VTC J095517.5+690813 (see Table 6), with few reaching a similar jet power (Pietka et al 2017;Fender et al 1999;Brocksopp et al 2007;Curran et al 2014;Tetarenko et al 2017;Dunn et al 2010). Another important difference to LMBXs is the lack of short-term radio variability displayed by VTC J095517.5+690813 within the four 1 hour epochs at which VTC J095517.5+690813 was detected.…”
Section: X-ray Binary or Imbhcontrasting
confidence: 56%
See 2 more Smart Citations
“…V404 Cyg, V6461 Sgr and H1743-322; Han & Hjellming 1992;Hjellming et al 2000;McClintock et al 2009) or periods of stable radio flux (GRS 1915+105;, which are more consistent with the timescale of VTC J095517.5+690813. However, typical LMXB minimum energies are also at least an order of magnitude lower than our estimate for VTC J095517.5+690813 (see Table 6), with few reaching a similar jet power (Pietka et al 2017;Fender et al 1999;Brocksopp et al 2007;Curran et al 2014;Tetarenko et al 2017;Dunn et al 2010). Another important difference to LMBXs is the lack of short-term radio variability displayed by VTC J095517.5+690813 within the four 1 hour epochs at which VTC J095517.5+690813 was detected.…”
Section: X-ray Binary or Imbhcontrasting
confidence: 56%
“…The VLA sampling of M81 did not resolve the initial rise in emission so we cannot adequately constrain its risetime. However, recent work by Pietka et al (2015Pietka et al ( , 2017 has demonstrated that a broad correlation exists between the peak radio luminosity and the variability timescales (rise/decline rates) of a transient. Using this relation, the measured peak radio luminosity of VTC J095517.5+690813 (νL ν = 8.7 × 10 33 erg s −1 ) is brighter than most XRB flares, with the correlation suggesting the transient should have had an exponential rise timescale (rise-time or e-folding time) of τ ∼ 2.6 d (see figure 7 of Pietka et al 2017, but note the scatter on the rise-time for XRBs, which is 10 −2 τ 10 3 days).…”
Section: Discussion: the Nature Of The Radio Transientmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to characterize the light curve for each individual spectral channel, we followed the thresholding approach of Pietka et al (2017). The background flux density level, b, and the signal variation due to noise, σ, were estimated from the preburst part of the light curve, that is, before MJD ∼56716.…”
Section: Observationsmentioning
confidence: 99%
“…The radio transient data used were collected by Pietka et al (2017) except for the kilonova light curve, which was collected by Dobie et al (2018).…”
Section: Radio Datamentioning
confidence: 99%